Ophiopogonin D promotes bone regeneration by stimulating CD31hiEMCNhi vessel formation. (20th February 2020) - Yang, Mi; Li, Chang‐Jun; Xiao, Ye; Guo, Qi; Huang, Yan; Su, Tian; Luo, Xiang‐Hang; Jiang, Tie‐Jian
Abstract: Objectives: CD31 hi EMCN hi vessels (CD31, also known as PECAM1 [platelet and endothelial cell adhesion molecule 1]; EMCN, endomucin), which are strongly positive for CD31 and endomucin, couple angiogenesis and osteogenesis. However, the role of CD31 hi EMCN hi vessels in bone regeneration remains unknown. In the present study, we investigated the role of CD31 hi EMCN hi vessels in the process of bone regeneration. Materials and Methods: We used endothelial‐specific Krüppel like factor 3 ( Klf3 ) knockout mice and ophiopogonin D treatment to interfere with CD31 hi EMCN hi vessel formation. We constructed a bone regeneration model by surgical ablation of the trabecular bone. Immunofluorescence and micro‐computed tomography (CT) were used to detect CD31 hi EMCN hi vessels and bone formation. Results: CD31 hi EMCN hi vessels participate in the process of bone regeneration, such that endothelial‐specific Klf3 knockout mice showed increased CD31 hi EMCN hi vessels and osteoprogenitors in the bone regeneration area, and further accelerated bone formation. We also demonstrated that the natural compound, ophiopogonin D, acts as a KLF3 inhibitor to promote vessels formation both in vitro and in vivo. Administration of ophiopogonin D increased the abundance of CD31 hi Emcn hi vessels and accelerated bone healing. Conclusions: Our findings confirmed the important role of CD31 hi Emcn hi vessels in bone regeneration and provided a new target to treat bone fracture or promote bone regeneration.